Welfare effects of R&D support policies - Tuomas Takalo; Tanja Tanayama; Otto Toivanen (Bank of Finland, 2017)
We conduct a welfare analysis of R&D subsidies and tax credits using a model of innovation policy in corporating externalities, limited R&D participation and finanial market imperfetions. We estimate the model using R&D projet level data from Finland. The optimal R&D tax credit rate (0.24) is lower than the average R&D subsidy rate (0.36). The intensive, not the extensive margin of R&D is important for poliy. Tax credits and subsidies inrease R&D investments and spillovers compared to laissez-faire but to levels below the first best. R&D support policies don't improve welfare.
URN:NBN:fi:bof-201710161631; Additional information: A revised version published on 18 Jan 2022 is available as BoF DP 2/2022.; More recent version: http://hdl.handle.net/10419/249598
Keywords: O38; O31; L53; C31; 330